If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1x + 12 = 10 + 7 Reorder the terms: 6 + 12 + -1x = 10 + 7 Combine like terms: 6 + 12 = 18 18 + -1x = 10 + 7 Combine like terms: 10 + 7 = 17 18 + -1x = 17 Solving 18 + -1x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1x = 17 + -18 Combine like terms: 18 + -18 = 0 0 + -1x = 17 + -18 -1x = 17 + -18 Combine like terms: 17 + -18 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| x+5=2x-13 | | 1/4(p-30 | | 3z=9z-18 | | (3a-2cd)-(2b+3cd)= | | 5G+21=11g | | 0.06x+0.03y=27 | | 0.06x+0.03y=277 | | log(x^3-11x)-logx=2 | | 2y=4y-6 | | Y=-16x+80x | | (a^3-2a^3)-(3a^2-4a^3)=equation | | 25x-1=625 | | -3x-5(5x+13)=78 | | 4y-1=25 | | 2x+2=-1x+26 | | ((m^6n)^-2(m^2n^-2)^3)/m^-1n^-2 | | 9x+4=-18 | | 2/4p=3/4p+2 | | 15/17-2/34 | | 40=6x+16 | | R(4)+8= | | 10=6x+16 | | 15x+20x=1800 | | 1.8+32=90 | | -8y+8=37x-7 | | -3(5x+-4)=21 | | (-7p/2)=(-7/8) | | 13x^2+21=-5x^2+22 | | (-7p/2)(-7/8) | | 32x=1 | | (2-7x)+(2x+1)= | | 2-4x=4x+10 |